Upf2-Mediated Nonsense-Mediated Degradation Pathway Involved in Genetic Compensation of TrpA1 Knockout Mutant Silkworm (Bombyx mori) - Wang, Dong-Yue; Zhu, Juan; Zhang, Yi-Zhong; Cui, Qian-Yi; Wang, Shan-Shan; Ning, Yang-Wei; Shen, Xing-Jia (Insects (Basel, Switzerland), 2024)
Genetic mutations leading to premature termination codons are known to have detrimental effects. Using the Lepidoptera model insect, the silkworm (Bombyx mori), we explored the genetic compensatory response triggered by mutations with premature termination codons. Additionally, we delved into the molecular mechanisms associated with the nonsense-mediated mRNA degradation pathway. CRISPR/Cas9 technology was utilized to generate a homozygous bivoltine silkworm line BmTrpA1−/− with a premature termination. Transcript levels were assessed for the BmTrpA paralogs, BmPyrexia and BmPainless as well as for the essential factors Upf1, Upf2, and Upf3a involved in the nonsense-mediated mRNA degradation (NMD) pathway. Upf2 was specifically knocked down via RNA interference at the embryonic stage. The results comfirmed that the BmTrpA1 transcripts with a 2-base deletion generating a premature termination codon in the BmTrpA1−/− line. From day 6 of embryonic development, the mRNA levels of BmPyrexia, BmPainless, Upf1, and Upf2 were significantly elevated in the gene-edited line. Embryonic knockdown of Upf2 resulted in the suppression of the genetic compensation response in the mutant. As a result, the offspring silkworm eggs were able to hatch normally after 10 days of incubation, displaying a non-diapause phenotype. It was observed that a genetic compensation response does exist in BmTrpA1−/− B. mori. This study presents a novel discovery of the NMD-mediated genetic compensation response in B. mori. The findings offer new insights into understanding the genetic compensation response and exploring the gene functions in lepidopteran insects, such as silkworms.